EDUCATIONAL ADMINISTRATION AS AN INSTRUMENT FOR SCHOOL DEVELOPMENT: A LITERATURE REVIEW - Nur Fahmuddin Hanif; Ziddan Arrauf; Idham Kholid; Yuniar Yuniar (Jurnal Multidisipliner Kapalamada, 2025)
The role of educational administration as a strategic instrument in school development, focusing on the function of managing and improving the quality of educational services. Through a systematic analysis of national and international literature, this study identified challenges faced by schools, such as policy changes, limited human resources and technology integration. The findings show that education administration can improve the quality of management and teacher performance, as well as the quality of education services if optimally implemented. However, administrative practices often fall short of their potential due to the lack of integration between theory and practice and the lack of adaptation to the local context. Therefore, this study recommends the need to strengthen institutional capacity through participatory approaches and effective use of information technology. As such, this study contributes to providing deeper insights into how education administration can function as an agent of change that has a positive impact on school development and the achievement of quality education.